UV-B Radiations and Secondary Metabolites - İlkay Yavaş; Aydın Ünay; Shafaqat Ali; Zohaib Abbas (Turkish Journal of Agriculture: Food Science and Technology)
Ultraviolet-B (UV-B: 280 to 320 nm) radiations have appeared to be detrimental to plants, due to their damaging effects on proteins, lipids, membranes and DNA. UV-B radiations are a significant regulator of plants’ secondary metabolites. High intensity of ultraviolet radiations may interfere with growth and productivity of crops. But low levels of UV-B radiations give rise to changes in the plants’ secondary metabolites such as phenolic compounds, carotenoids and glucoseinolates. Therefore, low intensity of UV-B radiations may be used to generate plants, enriched with secondary metabolites, having improved reproductive ability, early ripening and tolerance against fungi, bacteria and herbivores.